KANDUNGAN VITAMIN A ASI IBU NIFAS DI KABUPATEN SERANG - Dewi Permaesih; Yuniar Rosmalina (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
Vitamin A Breastmilk Postpartum Women In Kabupaten Serang.Background: Since the vitamin A status of most newborn is marginal, therefore, to avoid the infants suffering from vitamin A deficiency, it may be worth by ensuring that the concentration of retinol in breast milk is adequate.Objectives: To evaluate the effect of vitamin A supplementation on the concentration of retinol in breast milk of postpartum mothers.Methods: One hundred sixteen of postpartum mothers were randomly assigned to group 1 group 2. The mothers in group one (59 respondents) were given a single dose of vitamin A by 2 days consecutive, whereas the mothers in group two (57 respondents) were given double doses of vitamin A. Anthropometry, food consumption were assessed and maternal breast milk retinol level were serially assessed.Results: Breast milk retinol concentration showed greater at 24 h after supplementation in both groups. From 0.52 ± 0.29 umol/L in 0 h to 1.40 ± 0.65 umol/L in group 1 and from 0.41 ± 0.37 umol/L to 2.36 ± 0.89 umol/L in group 2. However, after 30 days of supplementation showed that the breast milk retinol concentration of both groups was lower then the zero hour concentration.Conclusions: Two ways vitamin A supplementation maintain higher breast milk retinol concentrabon of at least 30 days after supplementation.Keywords: retinol, postpartum, breastmilk